Euphoria and Social Media Related to Organizational Effectiveness, Based on Gangnam Style Case - Astadi Pangarso; Cut Irna Setiawati (Bandar Lampung University, 2015)
Social media is part of the information communication technology (ICT) which is important in human life currently. Social media is important because it play a role in the fulfillment of human needs, especially when associated with humans that was created as social creatures. As social creatures, humans build organizations to meet their needs to interact, communicate, collaborate and agree on a goal. In organizations, the organizational effectiveness has an important role in fulfilling the organization purposes. The presence of euphoria phenomenon may provide an explanation linkage between euphoria and organizational effectiveness. This study is a descriptive study, which aims to explain how social media is used as a media to convey the euphoria that contributes to the organizational effectiveness based on gangnam style case. The research method used to collect and analyze secondary data from the related literature study with the research journals. This research is expected to be the basis for future research which can be done empirically and contextually in term of social media that convey euphoria and contribute to organizational effectiveness.